Influence of Pre-x-ray Cryoeffect on the Growth of Guerin’s Adenocarcinoma in the Process of Irradiation - Uzlenkova, N. E.; Mikhanovsky, A. A. (Problems of Cryobiology and Cryomedicine, 2002)
The authors have studied the growth rates of Guerinâ€™s adenocarcinoma in the process of X-ray therapy depending on the performance terms of pre-x-ray tumour cryodestruction. The investigation results have demonstrated that the growth rate for the tumour in the irradiation process depends on the terms of cryodestruction performance. The cryoeffect 24 hrs prior to the X-ray therapy reduces the growth rate of Guerinâ€™s adenocarcinoma in the process of the whole irradiation. Cryodestruction 48hrs prior to the start of irradiation causes only a short-time delay in the tumour growth in the first 48hrsÂ after starting the irradiationÂ with its followingÂ accelerating.